A technology-specific process mining maturity grid for manufacturing and logistics - Dunzer, Sebastian; Zilker, Sandra; Weinzierl, Sven; Tang, Willi; Dieckmann, Felix; Stenglein, Simon; Rist, Johannes; Matzner, Martin (International Journal of Production Research, 2025)
Process mining applies data mining to the data produced in the slipstream of the executing process instances. Hence, it enables organisations gain transparency about how exactly the processes are executed. Organisations can use this transparency to find opportunities to improve their business processes, such as manufacturing and logistics. Previous research provides methodological guidance on how process mining projects can be conducted and how process mining capabilities can be assessed from an organisational perspective. However, organisations tend to lack experience with novel technologies, which is why they often miss out on opportunities to improve their operations using the insights gained through process mining. This study is the first to contribute to the existing literature by examining process mining capabilities from a technological perspective, focussing on the manufacturing and logistics domain. We conducted a systematic case study review and 12 semi-structured interviews with different manufacturing organisations to develop and validate our technology-specific process mining maturity grid for manufacturing and logistics. The resulting maturity grid is a tool for demonstrating development paths for the further application of process mining in organisations. The grid details maturity using three focus areas (i.e. data input, process mining utilisation, and integration) structured into five maturity level
Keywords: process mining; maturity grid; process improvement; manufacturing; logistics